Diagnostic and Prognostic Role of Procalcitonin in Infections - Maria Hatzistilianou (The Scientific World Journal)
Despite several consensus conferences, the criteria for the definition of sepsis are still considered too sensitive and insufficiently specific. The traditional clinical signs of infection and routine laboratory tests used to diagnose bacterial infection and sepsis lack diagnostic accuracy and can be misleading, particularly in patients with immunodeficiencies. The problems with sepsis definitions and diagnoses are indications of the need to focus on biochemical mediators capable not only of distinguishing the inflammatory response to infection from other types of inflammation, but also of indicating the severity and prognosis of the disease. Thus, physicians need an early and rapid marker for detecting bacterial infection and distinguishing it from viral infection. Several studies revealed that elevated procalcitonin (PCT) levels in human blood could be detected in cases of sepsis and bacterial infection. PCT is a protein that can act as a hormone and a cytokine. It can be produced by several cell types and many organs in response to proinflammatory stimuli, particularly bacterial infection. It provides a rapid diagnostic test, available at the patient's bedside, and its half-life is suitable for daily monitoring of the disease progress.